Treating of the Articular Cartilage in Rabbits Using Different Doses of Platelet-Rich Plasma - khaleefah, Mustafa; Emran, Hassanain A. (مجلة الانبار للعلوم البيطرية)
The current study was designed to evaluate the effects of autologous platelets rich plasma (PRP) on the articular cartilage repair. The present study was conducted on twenty-four adult male rabbits. Surgically (24) animals have received the same defect (5mm in diameter) which is made on the lateral condyle of the distal end of the femoral bone. The animals were divided randomly into three equal groups. Group (I) remain without treatment as a positive control group, group (II) which treated with a single dose of prepared PRP injected into the intraarticular space immediately after the creation of the of defect, group (III) treated with two doses of PRP (the first dose administered immediately after the surgery and second dose after (15) days of the first dose. Results were evaluated through the Biochemical analysis of the alkaline phosphatase (ALP) and Ca2+ at 15, 30, and 60 days after treatment. The biochemical findings of the current study showed that the total ALP was not significantly differed in animals of a group (II, III), whereas animals of a group (I) showed an elevation of ALP in the last period which indicates the osseous reaction especially in late stages of cartilage repair; however, the other two groups (II, III) didn’t show a great change in ALP levels in all periods of blood sample collection. The Ca+ levels also showed no significant differences among groups, only in the last period in the control positive group, so we concluded that the increase in ALP, and Ca+ levels in control group is an evidence of continues inflammatory process, and increase ability of ossification of the new tissue formed in the site of the lesion.